Proses Komunikasi Tokoh Agama dalam Membantu Umat Menghadapi Disonansi Kognitif Pergulatan Batin - Prakasa, Arvent; Setyanto, Yugih (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
Inner struggles are experiences commonly faced by religious individuals when deeply held beliefs come into tension with challenging life realities. Such conditions can be understood as manifestations of cognitive dissonance, defined as psychological discomfort arising from inconsistencies between beliefs and lived experiences. In this context, religious leaders play an important role through pastoral communication as a form of spiritual and interpersonal accompaniment. This study aims to examine how pastoral communication practiced by Catholic religious leaders helps believers reduce cognitive dissonance arising from inner struggles. Employing a qualitative approach with a case study method, data were collected through in-depth interviews with a Catholic religious leader and a believer experiencing inner conflict, and analyzed using thematic analysis. The findings indicate that pastoral communication emphasizing empathy, nonjudgmental acceptance, and narrative approaches creates a safe space for believers to express inner conflicts and reconstruct the meaning of their experiences. This communicative process enables believers to integrate faith with lived reality, thereby reducing inner tension. Theoretically, this study affirms the relevance of cognitive dissonance theory in the field of religious communication and highlights pastoral communication as an interpersonal communication practice that plays a significant role in empathetic and contextual spiritual accompaniment. Pergulatan batin merupakan pengalaman yang kerap dialami umat beragama ketika keyakinan iman yang diyakini berhadapan dengan realitas hidup yang penuh tekanan. Kondisi ini dapat dipahami sebagai bentuk disonansi kognitif, yaitu ketegangan psikologis akibat ketidaksesuaian antara keyakinan dan pengalaman hidup. Dalam konteks tersebut, tokoh agama memiliki peran penting melalui komunikasi pastoral sebagai bentuk pendampingan spiritual dan interpersonal. Penelitian ini bertujuan untuk memahami bagaimana proses komunikasi pastoral yang dilakukan oleh tokoh agama Katolik berperan dalam membantu umat mereduksi disonansi kognitif yang muncul dari pergulatan batin. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data diperoleh melalui wawancara mendalam dengan seorang tokoh agama Katolik dan seorang umat yang mengalami pergulatan batin, kemudian dianalisis menggunakan analisis tematik. Hasil penelitian menunjukkan bahwa komunikasi pastoral yang menekankan empati, penerimaan tanpa penghakiman, serta pendekatan naratif mampu menciptakan ruang aman bagi umat untuk mengekspresikan konflik batin dan menata ulang makna pengalaman hidup. Proses komunikasi tersebut membantu umat mengintegrasikan iman dengan realitas hidup sehingga ketegangan batin dapat direduksi. Secara teoretis, penelitian ini menegaskan relevansi teori disonansi kognitif dalam kajian komunikasi religius, serta menunjukkan bahwa komunikasi pastoral merupakan praktik komunikasi interpersonal yang berperan penting dalam pendampingan umat secara empatik dan kontekstual.